Adaptation of Digital Immigrant Lecturers Social and Politics Science Faculty Tanjungpura University in Intercultural Communication during the 4.0 Era - Wuysang, Julia Magdalena; Patriani, Ira; Rahmawati, Rahmawati; Pijoh, Feibe Engeline (Technium Social Sciences Journal, 2025)
This study aims to explore the adaptation of digital immigrant lecturers in intercultural communication during the 4.0 era in higher education in Indonesia. Since the COVID-19 pandemic, the digitalization of education has expanded rapidly, forcing lecturers to adapt to new technologies and online platforms. The primary challenge for digital immigrant lecturers lies in effectively communicating with digital native students, especially in a multicultural and technology-based context. This study identifies the role of intercultural communication in fostering constructive relationships between lecturers and students from diverse cultural backgrounds in digital classrooms. The research adopts an exploratory qualitative approach, utilizing a case study of lecturers and students at the Faculty of Social and Political Sciences, Tanjungpura University (UNTAN), Pontianak. Data were collected through in-depth interviews, participatory observation, and document analysis related to thesis guidance and online interactions. The data were analyzed using a thematic analysis approach to identify patterns of intercultural communication. The study draws on theories of Digital Generations, Face Negotiation, High and Low Context Cultures, and Uncertainty and Trust. The findings reveal that: 1) The inability of digital immigrant lecturers to master new technologies is associated with psychological, cultural, and social dimensions; 2) Tensions in face negotiation affect perceptions of value and professional status; 3) Limited intercultural understanding causes lecturers to feel that their dignity is undermined in the presence of students; 4) Technological uncertainty creates anxiety that threatens the professional face of digital immigrant.